Assessment of indoor and outdoor PM species at schools and residences in a high-altitude Ecuadorian urban center. (July 2016) - Raysoni, Amit U.; Armijos, Rodrigo X.; Weigel, M. Margaret; Montoya, Teresa; Eschanique, Patricia; Racines, Marcia; Li, Wen-Whai
Abstract: An air monitoring campaign to assess children's environmental exposures in schools and residences, both indoors and outdoors, was conducted in 2010 in three low-income neighborhoods in Z1 (north), Z2 (central), and Z3 (southeast) zones of Quito, Ecuador – a major urban center of 2.2 million inhabitants situated 2850 m above sea level in a narrow mountainous basin. Z1 zone, located in northern Quito, historically experienced emissions from quarries and moderate traffic. Z2 zone was influenced by heavy traffic in contrast to Z3 zone which experienced low traffic densities. Weekly averages of PM samples were collected at schools (one in each zone) and residences (Z1 = 47, Z2 = 45, and Z3 = 41) every month, over a twelve-month period at the three zones. Indoor PM2.5 concentrations ranged from 10.6 ± 4.9 μg/m 3 (Z1 school) to 29.0 ± 30.5 μg/m 3 (Z1 residences) and outdoor PM2.5 concentrations varied from 10.9 ± 3.2 μg/m 3 (Z1 school) to 14.3 ± 10.1 μg/m 3 (Z2 residences), across the three zones. The lowest values for PM10–2.5 for indoor and outdoor microenvironments were recorded at Z2 school, 5.7 ± 2.8 μg/m 3 and 7.9 ± 2.2 μg/m 3, respectively. Outdoor school PM concentrations exhibited stronger associations with corresponding indoor values making them robust proxies for indoor exposures in naturally ventilated Quito public schools. Correlation analysis between the school and residential PM size fractions and the various pollutant and meteorological parameters from central ambient monitoring (CAM) sites suggested varying degrees of temporal relationship. Strong positive correlation was observed for outdoor PM2.5 at Z2 school and its corresponding CAM site (r = 0.77) suggesting common traffic related emissions. Spatial heterogeneity in PM2.5 concentrations between CAM network and sampled sites was assessed using Coefficient of Divergence (COD) analysis. COD values were lower when CAM sites were paired with outdoor measurements (<0.2) and higher when CAM and indoor values were compared (>0.2), suggesting that CAM network in Quito may not represent actual indoor exposures. Highlights: Z2 (central) zone recorded elevated PM2.5 levels compared to Z3 (southeast) and Z1 (north) zones. Major PM10–2.5 sources are quarries, unpaved roads, agricultural activities, and soil erosion. The three study neighborhoods were impacted by varying traffic densities. Indoor-outdoor relationships for PM species were investigated at three schools. Central ambient monitoring sites may not be a good surrogate for understanding children's exposure in various exposure settings. Abstract : Outdoor school PM concentrations exhibited stronger associations with corresponding indoor values making them robust proxies for indoor exposures, especially in locations which lack significant indoor air pollution sources and have natural ventilation such as Quito public schools.